Dual-Task Treadmill Training for the Prevention of Falls in Parkinson's Disease: Rationale and Study Design - Mylius, Veit; Maes, Laura; Negele, Katrin; Schmid, Christine; Sylvester, Ramona; Brook, Caroline Sharon; Brugger, Florian; Perez-Lloret, Santiago; Bansi, Jens; Aminian, Kamiar; Paraschiv-Ionescu, Anisoara; Gonzenbach, Roman; et al. (Frontiers in Rehabilitation Sciences, 2022)
Various factors, such as fear of falling, postural instability, and altered executive function, contribute to the high risk of falling in Parkinson's disease (PD). Dual-task training is an established method to reduce this risk. Motor-perceptual task combinations typically require a patient to walk while simultaneously engaging in a perceptual task. Motor-executive dual-tasking (DT) combines locomotion with executive function tasks. One augmented reality treadmill training (AR-TT) study revealed promising results of a perceptual dual-task training with a markedly reduced frequency of falls especially in patients with PD. We here propose to compare the effects of two types of concurrent tasks, perceptual and executive, on high-intensity TT). Patients will be trained with TT alone, in combination with an augmented reality perceptual DT (AR-TT) or with an executive DT (Random Number Generation; RNG-TT). The results are expected to inform research on therapeutic strategies for the training of balance in PD.